2014
DOI: 10.1186/s12967-014-0219-9
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of the olive oil phenolic components oleuropein and hydroxytyrosol: focus on protection against cardiovascular and metabolic diseases

Abstract: The overall health beneficial action of olive oil phenolic components is well established. Recent studies have elucidated the biological effects of two isolated compounds, namely oleuropein and hydroxytyrosol, with particular attention on their antioxidant activity. Thus, a protective action has been demonstrated in preclinical studies against several diseases, especially cardiovascular and metabolic disorders.The present review will describe the biological effects of oleuropein and hydroxytyrosol, with partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
234
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 332 publications
(259 citation statements)
references
References 106 publications
(108 reference statements)
5
234
1
2
Order By: Relevance
“…[7][8][9][10][11][12] The in vitro antimicrobial activity of olive leaves has been reported by earlier researchers. 7, 13 Khalil et al reported that the aqueous olive leaf extract had the ability to produce stable silver nanoparticles possessing antibacterial activity against drug resistant pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] The in vitro antimicrobial activity of olive leaves has been reported by earlier researchers. 7, 13 Khalil et al reported that the aqueous olive leaf extract had the ability to produce stable silver nanoparticles possessing antibacterial activity against drug resistant pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Olive leave as a photochemical source of phenol and flavonoid [1] has antioxidant [2][3][4][5][6] and antibacterial [7][8][9][10] properties. Highest amount of phenol derivatives in olive leaf is oleuropein, whose amount depends on harvest time and varies between 17 and 23% [11].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, secoiridoid oleuropein (OLE) constitutes up to 6 -9% of dry matter in the leaves. It is also present in considerable amounts in drupes, while its concentration in virgin olive oil is significantly reduced due to the enzymatic degradation that occurs during olive processing [1][2][3][4] . Due to their health benefits, oleuropein, oleuropein derivatives, and seco-phenolic compounds are all considered to be important elements that make extra virgin olive oil a staple part of the Mediterranean diet.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their health benefits, oleuropein, oleuropein derivatives, and seco-phenolic compounds are all considered to be important elements that make extra virgin olive oil a staple part of the Mediterranean diet. Also, the compounds include the ability to scavenge reactive oxygen species (ROS) [5][6][7] , to inhibit the proliferation of several tumor cell lines [5,[8][9][10][11] , and also to protect against cardiovascular diseases [3,[12][13][14][15] and metabolic disorders as Diabetes mellitus [16][17][18][19] . In addition, they are effective in experimental models of age-related disorders, such as neurodegenerative diseases [14,20,21] .…”
Section: Introductionmentioning
confidence: 99%